PRESERVATION OF MEDICAL RECORDS- AN ESSENTIAL PART OF HEALTH CARE DELIVERY (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
The diagnostic reports, clinical as well as Para clinical care, medico-legal reports, birth and death certificates are various medical  records which are prepared in a hospital in the interest of patient, hospital and law the medical records required to be preserved  up to certain length of time and this article discussing the safe methods of preservation of medial record.
Keywords: Medical Record; Preservation; Micro Filming